Social Capital of Tobacco Farmer for Social Welfare Improvement - Fatwa Nurul Hakim; Gunawan Wibisono (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2017)
This research is aimed to reveal the social capital of tobacco farmers in supporting farming activities for increasing their social welfare. The social welfare of tobacco farmers is strongly influenced by the tobacco market prices. In this case, the cigarettes industry becomes the backbone of tobacco farming which supports the livelihood of tobacco farmers. This study uses the theory of Pierre Bourdieu and James Coleman on social capital. This is a qualitative research that uses case study approach. It was conducted at Lamuk Sub-village, Legoksari Village, Tlogomulyo Sub-District, TemanggungDistrict. Five informants of the research were selected purposively. The data were collected by using specific techniques of indepth interview. Then the data were analyzed by using interactive analysis namely omitting irrelevant data, presenting relevant data and making conclusion (verifying). The findings of this study indicate that the Indonesian Tobacco Farmers Association (APTI) and Farmers Group function as social networking; selametan ritual / pray for cultivating soil, taking care of tobacco plants and tasyakuran / ceremony for being grateful which function as the norm of trust; whilst labor relations system functions as reciprocity; and the activities of jimpitan sewu-selawe, mutual lending of labor, division of crops, watching the legislation of smoking prohibition, Djarum Foundation scholarship function as mutual benefit fromtobacco farmers to Legoksari rural society welfare. The result of the research describes that social capital functions as important aspect in empowering the society, especially the tobacco farmers and recommends that the Government, the society empowerment activists or the Society Empowerment Institutions, Ministry of Social RI, Local Government, and Agriculture Office need to support those related to farmers empowerment policy. It is also expected that the support needed will not change the society structure and will not omit the social capital values.